Satisfaction positively impacts customer loyalty and mediates the relationship between perceived service quality, perceived relationship quality, and customer loyalty, but does not mediate the relationship between perceived value and customer loyalty. - Bambang Dahris Sinaga; Alimuddin Rizal (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The research aims to explore the effect of perceived service quality, perceived relationship quality, and perceived value on loyalty, and to hypothesize that customer satisfaction serves as a mediator. This research approach is quantitative and has a direct type of cause. The sample of the research was comprised of 212 participants: pilgrims who were registered with PT Bank Permata, Tbk, in the East Java region. The information was gathered via a questionnaire, and analysis utilized the SEM-PLS and Sobel tests. The study's results indicate that perceived quality of service, perceived relationship quality, and perceived value directly affect customer satisfaction, all of which increase customer loyalty. Satisfaction positively impacts customer loyalty and mediates the relationship between perceived service quality, perceived relationship quality, and customer loyalty, but does not mediate the relationship between perceived value and customer loyalty. Keywords: Customer Satisfaction; Customer Loyalty; Perceived Service Quality; Perceived Relationship Quality; Perceived Value.